Penerapan Two-Factor Authentication Untuk Meningkatkan Keamanan Sistem Penjualan Akun Game Online - Salman Salman; Maspaeni Maspaeni; Supardianto Supardianto (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
The advancement of information technology has increased digital transaction activities, including online game account sales. However, transactions conducted manually through social media have high security risks such as account theft and fraud. This study aims to implement Two-Factor Authentication (2FA) in a web-based game account sales information system to enhance user access security. The system development method used is the waterfall method, which includes analysis, design, implementation, and testing stages. The system is developed using PHP and MySQL and integrated with an authentication mechanism based on One-Time Password (OTP). The results of Black Box testing show that the system functions according to requirements and improves login security. The implementation of 2FA minimizes unauthorized access risks, making the system more secure and reliable